Website Based Knowledge Management System To Manage Staff Knowledge In The Testing Service Laboratory SEAMEO BIOTROP - Zulkarnaen Noor Syarif; Fitria Rachmawati; Rio Kuncoro Sakti; Adi Afrian Wardianto; Muhammad Akhtar Hanif (Universitas Ibn Khaldun Bogor, 2024)
To support the process of disseminating knowledge between staff in the SEAMEO BIOTROP Testing Laboratory environment, an appropriate knowledge management system is needed and its existence is highly expected by staff because knowledge, documents, SOPs, regulations and experience in the SEAMEO BIOTROP Testing Laboratory environment have not been properly documented, making it difficult for employees. in carrying out their duties if personnel changes occur. The experience and knowledge of staff will be lost along with rotation, transfer, retirement or the end of the term of office of the staff concerned. Currently the knowledge and experience used in carrying out daily work is still stored with each staff, has not been translated into documents or systems, so it depends on each staff. The features produced by the knowledge management system to support the knowledge management process consist of document management, knowledge management, discussion forums and search features. The knowledge management system prototype has been tested using a user acceptance testing approach by SEAMEO BIOTROP Testing Laboratory staff, with overall results falling within the excellent score criteria with a percentage of 84.29%.